DESIGN AND DEVELOPMENT OF 2D VIDEO ANIMATION HISTORY OF VIETNAMESE VILLAGE IN BATAM - Jimmy Pratama; Wendy Aprianto (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Vietnamese Village in Batam is a former refugee village from Vietnamese natives in 1975 which received 250,000 refugees at that time. History also records that Indonesia government was assigned by the United Nations through UNHCR to turn Galang Island into a place of refuge or refuge for refugees from the Vietnam civil war that year, and the village of Vietnam is also a real witness to the history of Indonesia's services to victims of the Vietnamese civil war and now the government has made a Vietnamese village. this as a museum of historic humanity. This study aims to create a 2-dimensional animated video to introduce the history of the Vietnamese village as a nation's history that must be proud of. By using the Research and Development method. The research carried out was to observe and interview Vietnamese Village officials, then for the development stage using the MDLC (Multimedia Development Life Cycle) model. This research produces a short and clear 2-dimensional animated video with a duration of 4 minutes 16 seconds which will be implemented on social media such as YouTube. With this animated video, it is hoped that the community can add knowledge and insight into the history of the Vietnamese village, which the Indonesian population is very proud of.